INDUCED MUTATIONS IN HORSEGRAM (Macrotyloma uniflorum (LAM.)VERDC): CHLOROPHYLL MUTATIONS, MUTAGENIC EFFICIENCY AND EFFECTIVENESS: Life Science-Botany - SADASHIV N, BOLBHAT; VIKRAM D, BHOGE; KONDIRAM N, DHUMAL (International Journal of Life Science and Pharma Research, 2012)
Induction of mutation played a vital role in the crop improvement among modern methods of plant breeding. Genetic improvement through induced mutation was found to be very effective for variability in the quantitative and qualitative characters. With this view gamma radiation (100 to 600Gy), EMS (0.2 to 0.6%) and combinations of these treatments were used to induce variability in horsegram cv. Dapoli Kulthi-1. A wide range of chlorophyll mutations affecting all plant parts were isolated in M2 generation. The chlorophyll mutants were scored from 7 to 10 days after sowing. The different types of chlorophyll mutants such as albina, xantha, chlorina and viridis were reported due to the all mutagenic treatments. The high frequency of mutations in terms of mutants per 1000 M2 plant population were observed in low doses of EMS (0.2% and 0.3%), gamma radiation (100Gy) as well as in their combination (100Gy +0.2% and 100Gy + 0.3% EMS). Amongst all the treatments used EMS had induced the highest chlorophyll mutation frequency, followed by gamma radiations and combination treatments. The frequency of chlorophyll mutations in horsegram increased only up to certain dose/ conc. of the mutagens and there after decreased at higher dose/conc. In the present study, effectiveness of mutagenic treatments differed considerably. The mutagenic effectiveness showed a trend which was inversely proportional to the increasing doses/ concentration of mutagens. But in combination treatments it was reverse. Effectiveness and efficiency both are the important parameters to evaluate the usefulness of the mutagens. Effectiveness of the mutagen is the number of mutations produced per unit of the mutagen dose, while efficiency is the ratio of specific desirable mutagenic changes to undesirable effects such as lethality, sterility and seedling injury. The mutation rates were calculated based on the mean values of efficiency for each treatment. It has given an idea about the average rate of mutation induction per mutagen. The mutation rates based on the lethality, pollen sterility, seedling injury and effectiveness were recorded. The treatments of EMS were very effective than GR for inducing the highest mutation with reference to pollen sterility and effectiveness. Gamma radiation gave higher rate of mutations followed by EMS and combination treatments for lethality.